2015
DOI: 10.1186/s12896-015-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative whole-cell MALDI-TOF MS fingerprints distinguishes human monocyte sub-populations activated by distinct microbial ligands

Abstract: BackgroundConventionally, human monocyte sub-populations are classified according to surface marker expression into classical (CD14++CD16−), intermediate (CD14++CD16+) and non-classical (CD14+CD16++) lineages. The involvement of non-classical monocytes, also referred to as proinflammatory monocytes, in the pathophysiology of diseases including diabetes mellitus, atherosclerosis or Alzheimer’s disease is well recognized. The development of novel high-throughput methods to capture functional states within the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Gren et al using single-cell PCR gene expression identified 22 genes that are expressed by the classical population, 8 that characterize the intermediate population, and 6 that distinguish the non-classical population ( 32 ). Resting and activated monocyte subsets can be effectively distinguished using whole cell mass spectrometry fingerprinting ( 33 ). All these studies provide a platform to study further key details about monocyte phenotype and function, their behavior during disease and their interactions with pathogens.…”
Section: Circulating Monocytes and Their Subsetsmentioning
confidence: 99%
“…Gren et al using single-cell PCR gene expression identified 22 genes that are expressed by the classical population, 8 that characterize the intermediate population, and 6 that distinguish the non-classical population ( 32 ). Resting and activated monocyte subsets can be effectively distinguished using whole cell mass spectrometry fingerprinting ( 33 ). All these studies provide a platform to study further key details about monocyte phenotype and function, their behavior during disease and their interactions with pathogens.…”
Section: Circulating Monocytes and Their Subsetsmentioning
confidence: 99%
“…More advanced applications were aimed at distinguishing different cell types originating from the same cell lineage: identification of two different pancreatic hormone-secreting cell lines [36], the comparison of primary human blood cells and blood cell lines [37,38], molecular phenotyping of central nervous system (CNS) glial cells (astroglial, microglial and oligodendroglial) [39], and MALDI-MS fingerprinting of different melanoma cell lines [40]. Further applications of mammalian fingerprinting has focused on physiological changes of a single cell, reflecting its specific cell states or cell transformations such as differentiation of human colon carcinoma [41] or leukemia [38] cell lines, multifaceted activation of human macrophages [42], identification of resting and activated human monocyte subsets [43], rapid detection of apoptosis/necrosis signature [44], and monitoring of histone deacetylase drug target engagement [45]. Regardless of the scope of the aforementioned studies, no consistency in method parameters were observed (such as matrix, cell density, cell media, sample application technique, laser frequency/number of shots, etc) for either cell authentication [35][36][37][38][39][40] or close monitoring of a single cell changes applications [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Characterising the protein signatures of mammalian cells by MALDI-MS is less common when compared with lipid analysis; however it has been used for phenotypic screening of human cancer cell lines, 31,32 identification of cells within a co-culture 33,34 or tissues 35 and detection of transient changes within a specific cell type, such as immune cells. [36][37][38][39] However, many of these studies list dramatically different experimental procedures with several being adapted from existing biotyping protocols. The huge range of experimental parameters could therefore be problematic for translation of published assays to the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%